Antibacterial and antibiofilm activities of plant extracts against fusobacterium nucleatum - Juniarti, Devi Eka; Prasetyo, Eric Priyo; Tiara Anandita; Firdaus, Marsa Amalia; Swastika, Tesalonika Devanaya; Irma; Dayanti, Marisa Elvi; Ramadhan, Daniyal Lazuardi (Conservative Dentistry Journal, 2025)
Background: The pathogenicity of Fusobacterium nucleatum is more acknowledged these days. In the oral cavity, this bacterium plays a massive role in caries formation and periodontal problems such as periodontitis. The use of plant extract as an antibacterial or antibiofilm agent has grown in favor recently. Plant-derived extracts are said to be less toxic and to have comparable efficacy as their predecessors. Purpose: The goal of this article review is to provide an overview of the different bioactive substances found in plant extracts that are effective against Fusobacterium nucleatum. Review: In total 10 journals that fit the inclusion and exclusion criteria were chosen, with a total of 14 different plant extracts reviewed. MIC of the various extracts was found, where extract of lemongrass, purple leaf, Eucalyptus galbie, mulberry, and mangosteen was found at various concentrations. Conclusion: Each bioactive compound found on plant extracts holds their own mechanism in order to provide antibacterial behavior.